A Duty of Good Management? Protected Interests and the Employment Contract - Brodie, Douglas; Riley, Joellen (Victoria University of Wellington Law Review, 2019)
This essay in honour of Gordon Anderson's contribution to employment contract law reviews the extent to which it is true to say that the law of the employment contract does in fact protect the employee's interests in a well-managed workplace, where the harm suffered is financial or psychological/psychiatric. It will be suggested that the law has evolved less radically than Lord Slynn's dictum might suggest.